Odpowiedzi

Najlepsza Odpowiedź!
2010-01-13T02:02:26+01:00
A) (3x-2y)²=9x²-12xy+4y²
b) (x-4y)²=x²-8xy+16y²
c) (-6x+1)²=36x²-12x+1
d) (4x+6y)²=16x²+48xy+36y²
e) (2x-1)²=4x²-4x+1
f) (3x-2y)³=27x³-3*9x²*2y+3*3x*4y²-8y³=27x³-54x²y+36xy²-8y³
g) (-3x+2)³=-27x³+3*9x²*2-9x*4+8=-27x³+54x²-36x+8
h) (-5x-2y)³=-125x³-75x²*2y-15x*4y²-8y³=-125x³-150x²y-60xy²-8y³
i) (-3x-7)³=-27x³-27x²*7-9x*49-343=-27x³-189x²-441x-343
j) x²-4y²=(x-2y)(x+2y)
k) 25x²-16y²=(5x-4y)(5x+4y)
l) 36x²-y²=(6x-y)(6x+y)
ł) 8x³-1=(2x-1)(4x²+2x+1)
m) 125x³-27y³=(5x-3y)(25x²+15xy+9y²)
n) 64x³+8y³=(4x+2y)(16x²-8xy+4y²)
o) 216x³+y³=(6x+y)(36x²-6xy+y²)
p) (6x-1)²-2(x+3)(x-3)=36x²-12x+1-2(x²-9)=36x²-12x+1-2x²+18=
=34x²-12x+19
r) (x+2)³-(2x+1)² +(3x-1)(3x+1)=x³+6x²+12x+8-(4x²+4x+1)+9x²-1=
=x³+6x²+12x+8-4x²-4x-1+9x²-1=x³+11x²+8x+6
s) -2(3-x)²-2(3+x)²-(x-3)(x+3)=-2(9-6x+x²)-2(9+6x+x²)-x²+9=
=-18+12x-2x²-18-12x-2x²-x²+9=-5x²-27
t) (2x+1)³-(1-2x)³-(2x-1)(2x+1)=
=8x³+12x²+6x+1-(1-6x+12x²-8x³)-4x²+1=
=8x³+12x²+6x+1-1+6x-12x²+8x³-4x²+1=
=16x³-4x²+12x+1